SnS2@C Hollow Nanospheres with Robust Structural Stability as High-Performance Anodes for Sodium Ion Batteries - Shuaihui Li (Nano-Micro Letters, 2019)
Abstract Constructing unique and highly stable structures with plenty of electroactive sites in sodium storage materials is a key factor for achieving improved electrochemical properties through favorable sodium ion diffusion kinetics. An SnS2@carbon hollow nanospheres (SnS2@C) has been designed and fabricated via a facile solvothermal route, followed by an annealing treatment. The SnS2@C hybrid possesses an ideal hollow structure, rich active sites, a large electrode/electrolyte interface, a shortened ion transport pathway, and, importantly, a buffer space for volume change, generated from the repeated insertion/extraction of sodium ions. These merits lead to the significant reinforcement of structural integrity during electrochemical reactions and the improvement in sodium storage properties, with a high specific reversible capacity of 626.8 mAh g−1 after 200 cycles at a current density of 0.2 A g−1 and superior high-rate performance (304.4 mAh g−1 at 5 A g−1).